Léxico, cultura e identidade: protótipo de ensino para construção de um vocabulário da realidade campesina - Nobre, Kathiemi Matsumoto (2023)
This research is constituted as a pedagogical proposal essentially focused on the modality of rural education, seeking to value/strengthen the identity and the peasant struggle. In this sense, the study aims to value the lexical as one of the bases of cultural expression, since it is also an immaterial heritage and identity of its people. To this end, an action research was conducted with 22 9th grade students from a public school, located in a rural area of Ceilândia-DF, where the teacher-researcher works. A priori, a bibliographic research on the theme was carried out, bringing to the study basis normative documents that contributed to substantiate the work proposal presented, among them: the National Curriculum Parameters (BRAZIL, 1998), the Common National Curriculum Base (BRAZIL, 2017), the Pedagogical Guidelines for Basic Education in the Field (FEDERAL DISTRICT, 2019). Regarding the theorists, the following were fundamental: Freire (2011), Caldart (2012), Antunes (2012), Bezerra (1999), Biderman (1996), Souza (2014), Bakhtin (1997), Dolz; Schneuwly (2004), among others. The research was based on the power and the duty of the school to foster the process of identity, social and cultural appropriation of rural students. In th is sense, a didactic intervention proposal was elaborated with the objective of expanding the students' lexical and criticality through a comparative study in school dictionaries and in the Dicionário de Educação do Campo of words belonging to the peasant reality. Furthermore, activities involving the production of the discursive genre Memories Report were included, as an instrument of (re)construction and (re)affirmation of identity, because the study sustain that the work with the memorial rescue can promote more criticality and recognition of who they are. This research is also committed to multi-literacies, therefore the teaching prototype model, conceived by Rojo (2012), was used in the development of the didactic proposal as an instrument for the insertion of tools of new information and communication technologies. The results of the study showed that the intervention proposal brought positive impacts for the teaching-learning process of the students, because the applied activities contributed to the autonomy, enriched the lexical repertoire, improved the writing skills and contributed to the identity recognition and citizenship formation of the students.